Associations between body mass index and hospital resource use in patients hospitalised for COVID-19 in England: a community-based cohort study - Altunkaya, J; Piernas, C; Pouwels, K; Jebb, SA; Clarke, P; Astbury, N; Leal, J (Elsevier, 2024)
Background: Excess weight is a major risk factor for severe disease after infection with SARS-CoV-2. However, the effect of BMI on COVID-19 hospital resource use has not been fully quantified. This study aimed to identify the association between BMI and hospital resource use for COVID-19 admissions with the intention of informing future national hospital resource allocation. Methods: In this community-based cohort study, we analysed patient-level data from 57 415 patients admitted to hospital in England with COVID-19 between April 1, 2020, and Dec 31, 2021. Patients who were aged 20–99 years, had been registered with a general practitioner (GP) surgery that contributed to the QResearch database for the whole preceding year (2019) with at least one BMI value measured before April 1, 2020, available in their GP record, and were admitted to hospital for COVID-19 were included. Outcomes of interest were duration of hospital stay, transfer to an intensive care unit (ICU), and duration of ICU stay. Costs of hospitalisation were estimated from these outcomes. Generalised linear and logit models were used to estimate associations between BMI and hospital resource use outcomes. Findings: Patients living with obesity (BMI >30∙0 kg/m²) had longer hospital stays relative to patients in the reference BMI group (18∙5–25∙0 kg/m²; IRR 1∙07, 95% CI 1∙03–1∙10); the reference group had a mean length of stay of 8∙82 days (95% CI 8∙62–9∙01). Patients living with obesity were more likely to be admitted to ICU than the reference group (OR 2∙02, 95% CI 1∙86–2∙19); the reference group had a mean probability of ICU admission of 5∙9% (95% CI 5∙5–6∙3). No association was found between BMI and duration of ICU stay. The mean cost of COVID-19 hospitalisation was £19 877 (SD 17 918) in the reference BMI group. Hospital costs were estimated to be £2736 (95% CI 2224–3248) higher for patients living with obesity. Interpretation: Patients admitted to hospital with COVID-19 with a BMI above the healthy range had longer stays, were more likely to be admitted to ICU, and had higher health-care costs associated with hospital treatment of COVID-19 infection as a result. This information can inform national resource allocation to match hospital capacity to areas where BMI profiles indicate higher demand. Funding: National Institute for Health Research.